2019
DOI: 10.1002/lipd.12203
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Assessment of Dried Blood Spot Fatty Acid Compositions

Abstract: Dried blood spots for fatty acid profiling are increasing in popularity; however, variability in results between laboratories has not been characterized. Whole blood from two subjects (low and high n‐3 polyunsaturated fatty acid [PUFA] status) was collected, 25 μL applied to butylated hydroxytoluene (BHT)‐treated chromatography strips, dried in air, and shipped to five laboratories. Results were reported as “routine” (typical fatty acids for each laboratory) or “standardized” (a set of 19 fatty acids), and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Blood spots are also less invasive than other collection methods and have minimal field storage requirements [Ostler et al, 2014]. Here, consistent with only a handful of prior studies [Hewawasam et al, 2017;Metherel et al, 2019] we demonstrated ability to measure most PUFAs in such samples, stored for a period of up to 5 years.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Blood spots are also less invasive than other collection methods and have minimal field storage requirements [Ostler et al, 2014]. Here, consistent with only a handful of prior studies [Hewawasam et al, 2017;Metherel et al, 2019] we demonstrated ability to measure most PUFAs in such samples, stored for a period of up to 5 years.…”
Section: Discussionsupporting
confidence: 86%
“…The goal of this study was therefore to examine the association between ASD and PUFAs measured in newborns, using dried blood spot (DBS) samples. To our knowledge, this is the first study to examine neonatal PUFA levels in association with ASD, and one of only a few that has measured PUFAs in newborn bloodspots [Bell et al, 2011;Hewawasam, Liu, Jeffery, Muhlhausler, & Gibson, 2017;Metherel et al, 2019]. We also sought to examine the correlation between PUFA levels in maternal serum samples collected during mid-pregnancy and those in newborn bloodspots, to address potential variability in timing of measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of different analyte handling and preparation techniques as well as the intrinsic differences between complementary technologies and platforms has important implications for ensuring QC. The potential for further community-wide efforts, such as interlaboratory studies for GC and LC-MS-based lipid analyses, should continue to be explored, similar to what has previously been achieved in GC-MS-based metabolomics (Lin et al, 2020) and fatty acid methyl ester analysis (Metherel et al, 2019;Schantz et al, 2016). The creation of novel labeled standards that are designed for specific lipid classes, matrices and/ or applications will facilitate future harmonization studies through more accurate quantification.…”
Section: Standard Mixtures For Lipidomicsmentioning
confidence: 94%
“…A light breakfast snack was provided to all football players after the blood draw sessions. The dried blood spot testing (DBS) method was used for determining the DHA, EPA and n-3 Index (Anzalone et al, 2019;Metherel et al, 2019). Blood was withdrawn by trained phlebotomists in the presence of a Sports Medicine Physician.…”
Section: Dha and Epa And Omega-3 Index Analysismentioning
confidence: 99%